Establishment of enzyme-linked immunosorbent facilitated antigen binding as a biomarker assay for Japanese cedar pollen allergy immunotherapy - Chiharu Fukano; Katsuyo Ohashi-Doi; Kaare Lund; Atsuhito Nakao; Keisuke Masuyama; Tomokazu Matsuoka (Elsevier, 2019)
Background: Clinical efficacy of allergen-specific Immunotherapy (AIT) towards Japanese cedar (JC) pollen allergy is firmly established but JC pollen-specific biomarker assays are lacking. Treatment-related increase of allergen-specific antibodies is a robust biomarker of successful AIT. Allergen-specific non-IgE antibodies are believed to reduce the effects of allergen exposure by competing with IgE for allergen binding, and in-vitro assays quantifying the effects of AIT-induced IgE-blocking antibodies are advantageous. A cell-free enzyme-linked immunosorbent facilitated antigen binding (ELIFAB) assay of JC pollen was established. Methods: Serum IgE-allergen complexes were captured by immobilized recombinant CD23, and allergen-IgE-CD23 complexes were detected by a biotin-conjugated anti-human IgE antibody. Sera from JC pollen-allergic subjects without or with subcutaneous immunotherapy (SCIT) with JC pollen extract were used (n = 11/group). Results: Optimal assay conditions were established at 20 μg/mL CD23 and 0.3 μg/mL JC pollen extract, and the dependency on CD23 and IgE was verified. The data show that the JC pollen ELIFAB assay is fit for purpose and demonstrates that the IgE-blocking activity is significantly increased in the JC pollen SCIT group compared with the non-treated group. Conclusion: The JC pollen ELIFAB assay represents a simple, cell-free biomarker assay for monitoring the development of IgE-blocking antibody activity during JC pollen AIT. Keywords: Allergy immunotherapy, Allergic rhinitis, IgE-facilitated allergen presentation, Japanese cedar pollen, Subcutaneous immunotherapy